2021
DOI: 10.1177/14614448211062164
|View full text |Cite
|
Sign up to set email alerts
|

Digital contact does not promote wellbeing, but face-to-face contact does: A cross-national survey during the COVID-19 pandemic

Abstract: With restricted face-to-face interactions, COVID-19 lockdowns and distancing measures tested the capability of computer-mediated communication to foster social contact and wellbeing. In a multinational sample ( n = 6436), we investigated how different modes of contact related to wellbeing during the pandemic. Computer-mediated communication was more common than face-to-face, and its use was influenced by COVID-19 death rates, more so than state stringency measures. Despite its legal and health threats, face-to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 86 publications
1
34
0
Order By: Relevance
“…Recently, diverse issues have been raised in the research arena about the use of cameras when videoconferencing, such as: (1) why students turn their cameras on or off [ 25 , 26 , 35 , 36 , 37 ]; (2) the fatigue associated with videoconferencing [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ] and how to cope with this issue [ 41 , 45 , 46 , 47 ] or the development of a conceptual model about this topic [ 48 ]; (3) engagement or disengagement [ 49 , 50 , 51 ], a key element when analyzing learning [ 52 , 53 ]; (4) difficulties in maintaining attention [ 41 , 54 ]; (5) the emotions that result from using cameras in synchronous learning [ 55 ], including the stress [ 38 ] and anxiety caused by videoconferencing [ 56 , 57 , 58 ]; (6) privacy concerns [ 36 , 59 , 60 , 61 ]; (7) users’ preferences and comparisons when using F2F versus online formats [ 15 , 62 , 63 ]; or (8) guidelines and recommendations for users when videoconferencing [ 20 , 21 , 49 , 64 ], and even in a broader scope, analyzing on line learning through literature review approaches [ 65 , 66 ], or examining remote teaching in terms of its strengths, weaknesses, opportunities, and challenges [ 67 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, diverse issues have been raised in the research arena about the use of cameras when videoconferencing, such as: (1) why students turn their cameras on or off [ 25 , 26 , 35 , 36 , 37 ]; (2) the fatigue associated with videoconferencing [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ] and how to cope with this issue [ 41 , 45 , 46 , 47 ] or the development of a conceptual model about this topic [ 48 ]; (3) engagement or disengagement [ 49 , 50 , 51 ], a key element when analyzing learning [ 52 , 53 ]; (4) difficulties in maintaining attention [ 41 , 54 ]; (5) the emotions that result from using cameras in synchronous learning [ 55 ], including the stress [ 38 ] and anxiety caused by videoconferencing [ 56 , 57 , 58 ]; (6) privacy concerns [ 36 , 59 , 60 , 61 ]; (7) users’ preferences and comparisons when using F2F versus online formats [ 15 , 62 , 63 ]; or (8) guidelines and recommendations for users when videoconferencing [ 20 , 21 , 49 , 64 ], and even in a broader scope, analyzing on line learning through literature review approaches [ 65 , 66 ], or examining remote teaching in terms of its strengths, weaknesses, opportunities, and challenges [ 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different online learning experiences driven during the COVID-19, such as ZOOM cohort chats [ 82 ] adopted during the COVID-19 crisis, have had a positive effect on students’ well-being and student satisfaction levels [ 83 ]. However, face-to-face contact seems to benefit well-being more than computer-mediated interactions, as posited in [ 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…We determined the required sample size for a two parallel mediators model using a Monte Carlo Power analysis (Schoemann et al, 2017). Based on previous investigations with similar variables COVID-19 WORRY AND WELL-BEING 7 (Newson et al, 2021;Prati, 2021), we assumed small to moderate effect sizes (i.e., r = .13). The sample size needed to achieve 80% power was 800.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…However—as millions of people have recently discovered [ 1 ]—the advantages of video conferencing can come at a cost. The use of computer mediated communication during the pandemic lockdown was associated with poor mental well-being [ 2 ], and resulted in communication across organizations becoming more ‘siloed and stilted’ [ 3 ]. In a study of over a thousand video conferences, it was found turning the camera on (compared to leaving it off) caused feelings of daily fatigue that impacted engagement and could last until the following day [ 4 ].…”
Section: Introductionmentioning
confidence: 99%